HOMER AND VIRGIL IN MACROBIUS’ SATURNALIA: A LITERARY AGÓN (Argos, 2015)
Macrobius dedicated his text Saturnalia (V A.D) to the discussion of Virgil’s figure and literary works, building him as a paradigm of knowledge through the comparison with the other great magister of Antiquity: Homer. The purpose of the present paper is to analyze this macrobian operation in order to establish which of the two poets gets the first place in this friendly agón. Though the starting point seems to be the valuation of the literary skills of each contestant, the competence is solved appealing to the practice of imitatio, a main virtue in Late Antiquity and in Macrobius work.
Keywords: Late Antiquity; Saturnalia; literary agon; Homer; Virgil